Migration Citizenship Labour : Latin American World-Makers Resisting Crisis in Madrid - Jüssen, Lara (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2017)
Lara Jüssen takes the case of Latin American household and construction workers in Madrid to show how ir/regular labour migrants make citizenship available for themselves through emplacements, embodiments and enactments of citizenship. After describing the sociopolitical context of crisis and resistance in Spain, citizenship is anthropologized in order to approach it through the workplace: the private household and the construction site. Based on empirical results from interviews, it is analyzed how citizenship is emplaced through ego-centered networks and assemblages that situate the migrants' social belonging; how it is embodied through carving out of identities of the migrant workers, intersectionality of gender, ethnicity, and class, affects that imprint workers' bodies, and experiences of violence at the workplace; then citizenships' enactment is scrutinized through workers' empowerment for rights, individually at the workplace and collectively through demonstrations and political theater performance in urban public space. Contents Latin American labour migration to Madrid Citizenship theory Actor-centered approach based on emplacement, embodiment, and enactment of citizenship Social relations at the workplace Target Groups Scholars of migration sociology, anthropology, and social sciences Practicioners interested in political economy, gender, labour, and migration studies The Author Lara Jüssen is a cultural and social anthropologist with specialization in migration sociology.
Keywords: Social sciences.; Political sociology.; Human body -- Social aspects.; Emigration and immigration.; elektronické knihy; electronic books